Pangasinan restoration gets P34M - Cardinoza, Gabriel L. (2017)
The provincial government received a P33.9-million grant from the Tourism Infrastructure and Tourism Infrastructure and Enterprise Zone Authority for the completion of Casa Real (Royal House) in Lingayen town.
Keywords: Casa Real (Lingayen Pangasinan); Pangasinan (Philippines) -- Tourism & economic development